Analisis Tafsir Tematik terhadap Ayat Ayat Wakaf dalam Alqur'an dan Relevansinya dengan Kesejahteraan Ummat - Rizky Syah Putra; Erliani Syafitri Nasution; Septia Nur Hidayah; Alhafiz Alhafiz; Adzin Aziz Ahmad; Adinda Trya Izni (Pusat Riset dan Inovasi Nasional, 2024)
Waqf is one of the instruments of Islamic philanthropy that plays a strategic role in building sustainable welfare for the people. Although the term waqf is not explicitly mentioned in the Qur'an, its basic values are scattered throughout various verses that talk about infaq, almsgiving, distribution of wealth, and social justice. This article aims to analyse Qur'anic verses that have a substantial connection with the concept of waqf through a thematic (maudhu'i) interpretation approach, as well as to examine its relevance to efforts to improve the welfare of the ummah in a contemporary context. This study uses a qualitative-descriptive literature review method, drawing on the Qur'an, classical and contemporary interpretations, and scientific literature related to waqf and Islamic economics. The results of the study show that the principle of waqf in the Qur'an emphasises the sustainability of benefits, the trustworthiness of asset management, and an orientation towards social justice, all of which are relevant to the development of productive waqf as a solution for the welfare of the modern community.